DETERMINAN KREATIVITAS GURU SEKOLAH DASAR PASCA PENDIDIKAN DAN LATIHAN PROFESI GURU - Slameto, Slameto (Jurnal Penelitian Humaniora, 2019)
The 112 Semarang State University Rayon 2017 held 6 stages ofTPET (Teacher Professional Education and Training which eachstage consistsof 6 classes) for elementary school teachers. One ofthe goals is toincrease the creativity of theparticipants. Theproblem in this study ishow effective is TPET in increasing teachercreativity? Given that thereare many factors that influence teachercreativity as a manifestation of thesuccess of the TPET, in themanagement of education and training, one ofthe determiningfactors needs to be chosen; which in this study is limitedto theinternal factors of the teacher in question, namely: (1)independence, (2) teacher's understanding and (3) teacherdiscipline after theTPET. The next problem, among others:independence, Teacher's understanding and (3) discipline, whichfactors determine the effectiveness ofTPETin increasing teachercreativity? Data was collected with a rating scale that has beentested valid and reliable.TPETis effective in shaping teachercreativity. There is only 1 predictor variable, namely teachingdiscipline which is a determinant of teacher creativity. Teacherdiscipline influences (positive and significant) on teacher creativityby 35.80%. Both variables: understanding and independence areexcluded from this model.